2010
DOI: 10.1007/jhep09(2010)085
|View full text |Cite
|
Sign up to set email alerts
|

Light dark matter in the NMSSM: upper bounds on direct detection cross sections

Abstract: In the Next-to-Minimal Supersymmetric Standard Model, a bino-like LSP can be as light as a few GeV and satisfy WMAP constraints on the dark matter relic density in the presence of a light CP-odd Higgs scalar. We study upper bounds on the direct detection cross sections for such a light LSP in the mass range 2 − 20 GeV in the NMSSM, respecting all constraints from B-physics and LEP. The OPAL constraints on e + e − → χ 0 1 χ 0 i (i > 1) play an important rôle and are discussed in some detail. The resulting upper… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 85 publications
(130 reference statements)
1
23
0
Order By: Relevance
“…Therefore, the presence of light pseudoscalars in this JHEP07 (2014) model aides in making the annihilation of the relics efficient, avoiding an overabundance of the DM particles. The DM mass obtained in this analysis is significantly smaller than most MSSM neutralino-like proposals, and it is also consistent with the studies of light DM in the NMSSM [52,[59][60][61][62]. The final products from the annihilation of this light neutralino arelℓ pairs or lightqq pairs.…”
Section: Jhep07(2014)087supporting
confidence: 88%
See 1 more Smart Citation
“…Therefore, the presence of light pseudoscalars in this JHEP07 (2014) model aides in making the annihilation of the relics efficient, avoiding an overabundance of the DM particles. The DM mass obtained in this analysis is significantly smaller than most MSSM neutralino-like proposals, and it is also consistent with the studies of light DM in the NMSSM [52,[59][60][61][62]. The final products from the annihilation of this light neutralino arelℓ pairs or lightqq pairs.…”
Section: Jhep07(2014)087supporting
confidence: 88%
“…This favors a light DM candidate, with mass below 20 GeV, in the PQ limit or when a continuous R-symmetry is imposed. In such class of models, the relic density is obtained through annihilation into a light scalar or a pseudoscalar Higgs boson [52,[59][60][61][62].…”
Section: A Dark Matter Candidatementioning
confidence: 99%
“…, χ 0 5 ), with interesting implications for dark matter searches (see, e.g., refs. [72][73][74][75][76][77][78][79]). …”
Section: Jhep02(2014)048mentioning
confidence: 99%
“…Thus some attempts were made to account for them, for example with neutralinos lighter than, say, 15 GeV. In recent publications the authors of [7][8][9][10][11][12] considered and investigated the occurrence of light neutralino within the Minimal Supersymmetric Standard Model (MSSM) and Next-to-Minimal Supersymmetric Standard Model (NMSSM) while respecting several constraints. It was shown that an MSSM explanation for the signal is seriously challenged by collider searches and measurements in the flavour sector [7,8,13,14].…”
Section: Jhep12(2011)055mentioning
confidence: 99%